Does Literature Matter Today? Thoughts of the Outside. Issue 1 (April 2018) - Xie, Shaobo
Abstract : The paper celebrates the publication of Ranjan Ghosh and J. Hillis Miller's Thinking Literature across Continents as a significant event in the age of neoliberalism. It argues that, in spite of the different premises and the resulting interpretative procedures respectively championed by the two co-authors, both of them anchor their readings of literary texts in a concept of literature that is diametrically opposed to neoliberal rationality, and both impassionedly safeguard human values and experiences that resist the technologisation and marketisation of the humanities and aesthetic education. While Ghosh's readings of literature offer lightning flashes of thought from the outside of the Western tradition, signalling a new culture of reading as well as a new manner of appreciation of the other, Miller dedicatedly speaks and thinks against the hegemony of neoliberal reason, opening our eyes to the kind of change our teaching or reading of literature can trigger in the world, and the role aesthetic education should and can play at a time when the humanities are considered 'a lost cause'.